2006
DOI: 10.1074/jbc.m513225200
|View full text |Cite
|
Sign up to set email alerts
|

RANKL Stimulates Inducible Nitric-oxide Synthase Expression and Nitric Oxide Production in Developing Osteoclasts

Abstract: Normal bone remodeling requires a homeostatic balance between the activities of bone-forming osteoblasts and bone-resorbing osteoclasts (OCs).3 Excessive OC bone resorption leads to bone loss in many skeletal pathologies such as rheumatoid arthritis, periodontal disease, postmenopausal osteoporosis, implant osteolysis, and tumor-associated bone loss (1). OCs develop from hematopoietic precursors that fuse and differentiate into multinucleated bone-resorbing OCs in response to the essential tumor necrosis facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
36
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(40 citation statements)
references
References 49 publications
4
36
0
Order By: Relevance
“…Excessive amounts of NO may contribute to tissue destruction in periodontitis [32] and increased NO reflected more-severe inflammation [29]. This could be partly due to NO restraining influence to osteoclastogenesis [33]. In the present study, we observed the trend of NO to decrease over periods of archwire changes.…”
Section: Discussionsupporting
confidence: 60%
“…Excessive amounts of NO may contribute to tissue destruction in periodontitis [32] and increased NO reflected more-severe inflammation [29]. This could be partly due to NO restraining influence to osteoclastogenesis [33]. In the present study, we observed the trend of NO to decrease over periods of archwire changes.…”
Section: Discussionsupporting
confidence: 60%
“…Consistent with proposed hypotheses [10], [12], [20] and experimental observations [13], [19], [21]- [25], the mathematical model employed here, presented in [1], links the mechanical loading with the bone remodeling process through the mechanotransduction activity of osteocytes. See Fig.…”
Section: Functional Adaptation Of Bonesupporting
confidence: 52%
“…Nitrates may also affect osteoclasts and osteoblasts; NO may influence osteoclast activity, in part, via the receptor activator of NF‐kappaB ligand (RANKL)/osteoprotegerin (OPG) pathway. High levels of NO stimulate OPG, which binds to RANKL and prevents the binding of RANKL to the receptor activator of NF‐kappaB (RANK), decreasing osteoclast activity 48. eNOS global knockout animals exhibit lower BMD, bone formation, and osteoblast activity; with little to no effect on bone resorption, suggesting NO may be important for osteoblast function 49, 50.…”
Section: Discussionmentioning
confidence: 99%